Efektivitas Program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kantor Pertanahan Kabupaten Aceh Tengah - Humaira, Humaira; Rangkuti, Mohammad Ridwan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to find out and analyze how the PTSL program at the Central Aceh District Land Office is running. The research method used a qualitative research method with a descriptive approach. Data collection techniques were carried out by interviews, observation, documentation and literature study. Informants came from the PTSL program implementation team, namely the physical and juridical task force, village committee and the community who participated in program implementation. The results of the study show that there are two problems in implementing the PTSL program in Central Aceh District, namely; first, the slow process of distributing certificates to the public. Second, the community complained about being quoted the cost of preparing for the implementation of the program as an operation in the village. The long implementation of the program was due to a lack of communication and coordination that existed between the implementing committee, namely the village and the Central Aceh District Land Office committee. Meanwhile, the preparation costs quoted from the community were in accordance with applicable regulations, namely a maximum quotation of Rp. 250,000 per plot of land and an additional Rp. 50,000 if there is no basis for land right. There are no other citations outside of the regulations, so there is no indication of extortion in the implementation of the program caused by the leadership of the Head of the Land Office who gave a firm warning to both the office implementing committee and the committee in the village implementing the program.